(untitled) - Kaisler, Stephen H. (Hoboken, 2005)
Software Paradigms provides the first complete compilation of software paradigms commonly used to develop large software applications, with coverage ranging from discrete problems to full-scale applications. The book focuses on providing a structure for understanding a hierarchy of software development approaches, and showing the relationships between the different models.
Keywords: Computer software; Development; United States